HYBRID RETIREMENT AND ITS REGULATION BY CONSTITUTIONAL AMENDMENT NO. 103/2019 AND NORMATIVE INSTRUCTION NO. 151/2023 - Araújo , Antônio Hernandes de Sousa; da Costa, Edilson Dias; Silva, Ana Carolinna Barros; Lustosa, Thalita Furtado Mascarenhas; do Rego, Elson José; Santos, Jane Karla de Oliveira (Seven Editora, 2025)
The study addresses the types of retirement that make up the General Social Security Regime, a fundamental right guaranteed by Social Security. Initially, it seeks to understand the aspects of social security, bringing essential explanations for the development and understanding of work. Next, the granting of retirement and the transition rules introduced by the Social Security Reform, established by Constitutional Amendment No. 103/2019, are analyzed. Finally, the work emphasizes hybrid retirement, which mixes urban retirement with rural retirement, created through Law No. 11,718/2008 and analyzed with Normative Instruction No. 151/2023 after many discussions and several debates in the courts to update the granting of the benefit, so the present work carries out a study based on legislation, jurisprudence, academic works and scientific articles. DOI: https://doi.org/10.56238/sevened2025.018-012